Facilitating access to primary care for people living in socio-economically vulnerable circumstances in Belgium through community health workers: towards a conceptual model - Caroline Masquillier; Theo Cosaert (BMC Primary Care, 2023)
Abstract Introduction Inspired by examples in low- and middle-income countries, 50 community health workers (CHWs) were introduced in Belgium to improve access to primary care for people living in socio-economically vulnerable circumstances. This article aims to explore the ways in which CHWs support people living in socio-economically vulnerable circumstances in their access to primary care. Methods The qualitative research focuses on the first year of implementation of this pioneer nationwide CHW programme in Belgium. To respond to the research aim, thirteen semi-structured in-depth interviews were held with people living in socio-economically vulnerable circumstances. In addition, a photovoice study was conducted with fifteen CHWs comprising four phases: (1) photovoice training; (2) participatory observation with each CHW individually; (3) an individual semi-structured in-depth interview; and (4) three focus group discussions. The transcripts and the observation notes were analysed in accordance with the abductive analysis procedures described by Timmermans and Tavory. Results The qualitative results show that the CHWs’ outreaching way of working allows them to reach people living at the crossroads of different vulnerabilities that are intertwined and reinforce each other. They experience complex care needs, while at the same time they face several barriers that interrupt the continuum of access to primary care – as conceptualised in the theoretical access-to-care framework of (Levesque et al. Int J Equity Health. 12:18, 2013). Building on the theoretical access-to-care framework described by (Levesque et al. Int J Equity Health. 12:18, 2013), the conceptual model outlines first the underlying mechanisms of CHW-facilitated access to primary care: (I) outreaching and pro-active way of working; (II) building trust; (III) providing unbiased support and guidance in a culturally sensitive manner; and (IV) tailoring the CHWs’ approach to the unique interplay of barriers at the individual and health system level along the access-to-care continuum as experienced by the individual. Further disentangling how CHWs provide support to the barriers in access to care across the continuum and at each step is outlined further in the process characteristics of this conceptual model. Furthermore, the qualitative results show that the way in which CHWs support people is also impacted by the broader health system, such as long waiting times and unwelcoming healthcare professionals after referral from a CHW. Discussion The conceptual model of CHW-facilitated access to primary care developed in this article explores the way in which CHWs support people living in socio-economically vulnerable circumstances in their access to primary care in Belgium. Through their outreaching method, they play a valuable bridging role between the Belgian healthcare system and people living in socio-economically vulnerable circumstances.